Impact of Mobile Application Compatibility, Online Shopping and Payment on the User Satisfaction in Pakistan Context: Mediating role of Social Networking Site Adoption - Sajida Awais; Dr. Zaeem Yasin; Fatima Raza (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study aims to examine the adoption of mobile commerce in Pakistan by specifically considering the impact of mobile application compatibility, online shopping and online payment on its user satisfaction. This study is also an informative source to critically examine the mediating role of social media networking site adoption within these variables' relationship by covering the previous studies' gaps. To fulfill this aim, an online survey-based quantitative research design approach was used with a sample size of 427 (M = 237, F = 190) and a simple random sampling strategy was adopted. The sample consisted of people who actively used social media sites and mobile apps for online shopping. After collecting their reliable outcomes, the SPSS and smart PLS software utilized in analysis the reliable outcomes of which depicted that there is a significant impact of mobile application compatibility, online shopping and online payment on the user satisfaction for adopting mobile commerce under the mediating role of Social Networking Sites (SNS) adoption in Pakistan context. The study at hand is an authentic and reliable source of information because of its managerial and theoretical implications in the field of m-commerce. In addition to this, there is also an opportunity in front of upcoming scholars to cover its methodological and contextual gap in their future studies.